Тhe concept of character (behavior) in the poems of abai (Eurasian Journal of Philology Science and Education, 2023)
The article discusses the concept of behavior and character of a person reflected in the poetry of Abai. In modern domestic linguistics and literary criticism, there are many significant research works devoted to the term of the concept in its various aspects, but the concept of personality behavior in the context of poetics has not yet become the object of comprehensive analysis and study. The very concept of the character and behavior of an individual is a complex phenomenon that includes manners of action and conversation, moral education that begins with the individual and forms a stereotype of the behavior and character of the whole nation.The poetry of Abai is one of the valuable sources of information showing the essence of the character and behavior of a person of his time at a conceptually poetic level. The descriptive and evaluative conclusions of the poet, starting from universal human virtues and misdeeds to the behaviors and actions of certain sections of society (tore (special class of people in Kazakh Khanate), bai (rich people), common people) are relevant to this day. Therefore, in this article, the character and behavior of a person in the poet's poetry is considered as a set of actions and moral attitudes, interpreted at the level of thick and thin concepts. The poet almost never calls a person simply good and bad, he masterfully conveys everything with a detailed description of the manner and actions of the individual. Abai does not use "subtle" obvious concepts, his poems reflect complex author's concepts that originate from the depths and provide information about the human essence of an entire people of a certain historical period.